Comparison of performance and anthropometric parameters in paediatric competitive athletes during COVID-19 pandemic in the Czech Republic - Pastucha, Dalibor; Štěpánek, Ladislav; Botek, Michal; Filipčíková, Radka; Zapletalová, Jana; Hudec, Štěpán; Horáková, Dagmar (Central European journal of public health, 2023)
OBJECTIVES: In 2020, measures against the spread of COVID-19 were adopted, including nationwide school closures, restrictions on the free movement of persons and leisure time sports activities. The aim was to assess the impact of COVID-19-associated restrictions on the performance of paediatric and adolescent competitive athletes by comparing basic anthropometric and performance parameters. METHODS: The sample comprised 389 participants (115 girls, 274 boys). All participants were examined during regular preventive sports health checks from September to November 2019 and a year later. At the initial examination, the mean age of the entire sample was 12.2 ± 2.7 years (median 12.0, minimum 7.0; maximum 17.0). The examination consisted of a complete medical history and physical examination including maximal exercise testing on a leg cycle ergometer. RESULTS: In the entire sample, as well as in the boy and girl subgroups, body height, weight, body mass index (BMI), BMI percentile, and power output significantly increased according to a percentile graph for boys and girls in 2020. A reduction in power output (W/kg) was found. By 2020, W/kg dropped in 56.4% of the youngest participants (7-13 years), 75% of those aged 14-16 years and 64.9% of the oldest individuals (16-17 years). The percentage of the youngest children with power output reductions was statistically significantly lower than the percentages of the other age subgroups (p = 0.007). There were no significant differences in results between genders. CONCLUSIONS: Performance and anthropometric parameters worsened especially among older children. This should be reflected when planning epidemic measures in case of any similar situation in the future.
Keywords: Female; Anthropometry; dítě; ženské pohlaví; Adolescent; anti-epidemic measure; athlete; lidé; sport; antropometrie; COVID-19; pandemie; physical activity; Male; Czech Republic; index tělesné hmotnosti; sportovci; Česká republika; Child; Athletes; cardiovascular performance; mužské pohlaví; Body Mass Index; Pandemics; mladiství; Humans